2003
DOI: 10.1177/197140090301600320
|View full text |Cite
|
Sign up to set email alerts
|

Proton MR Spectroscopic Imaging in Pelizaeus-Merzbacher Disease

Abstract: BACKGROUND AND PURPOSE: Pelizeaus-Merzbacher disease (PMD) is a clinically and molecularly heterogeneous disorder linked to deletion, mutations, or duplication of the proteolipid protein (PLP1) gene locus at Xq22. The current study was conducted to characterize the results of proton MR spectroscopic (MRS) imaging in PMD.METHODS: Three boys with PMD (one with the severe connatal form and two with a more mild clinical phenotype [spastic paraplegia type 2]). and three age-matched healthy control subjects (age ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…PelizaeusMerzbacher disease has also been associated with alterations in NAA and NAAG levels in brain or cerebrospinal fluid. Increased levels of NAA in white matter have been reported by some researchers (Hanefeld et al, 2005;Takanashi et al, 2002), whereas other studies have reported decreased levels of NAA in white matter in this dysmyelinating disease (Pizzini et al, 2003). Increased NAAG in the cerebrospinal fluid has also been reported in patients with Pelizaeus-Merzbacher disease (Burlina et al, 2006a).…”
Section: Other Genetic Disruptions In Myelinogenesismentioning
confidence: 79%
“…PelizaeusMerzbacher disease has also been associated with alterations in NAA and NAAG levels in brain or cerebrospinal fluid. Increased levels of NAA in white matter have been reported by some researchers (Hanefeld et al, 2005;Takanashi et al, 2002), whereas other studies have reported decreased levels of NAA in white matter in this dysmyelinating disease (Pizzini et al, 2003). Increased NAAG in the cerebrospinal fluid has also been reported in patients with Pelizaeus-Merzbacher disease (Burlina et al, 2006a).…”
Section: Other Genetic Disruptions In Myelinogenesismentioning
confidence: 79%
“…In some patients there is a tigroid or patchy T2-hyperintensity that involves the supratentorial white matter as well as the cerebellum and brainstem. This pattern is more common in those with SPG II, whereas the confluent white matter is more common in the severe connatal form 26 . Loss of white matter volume and atrophy occur with time.…”
Section: Pelizaeus-merzbacher Disease (Pmd)mentioning
confidence: 88%
“…Loss of white matter volume and atrophy occur with time. Pathologically this correlates with axonal loss, for which MRS has been useful by showing a decrease in levels of NAA due to neuronal axonal degeneration, whereas on spectroscopy elevated levels of choline and creatine appear to arise from the increased astrocytic processes 26 .…”
Section: Pelizaeus-merzbacher Disease (Pmd)mentioning
confidence: 98%
“…By contrast, decrease in Cho or increase in Cr can be detected in hypomyelination [54]. In dysmyelinating diseases such as the Pelizaeus-Merzbacher disease, both increases and decreases in Cho have been described [12,55].…”
Section: Demyelinating and Dysmyelinating Diseasesmentioning
confidence: 99%